2018
DOI: 10.1177/2048872618805486
|View full text |Cite
|
Sign up to set email alerts
|

Real-life use of left ventricular circulatory support with Impella in cardiogenic shock after acute myocardial infarction: 12 years AMC experience

Abstract: Aims: Mortality in cardiogenic shock patients remains high. Short-term mechanical circulatory support with Impella can be used to support the circulation in these patients, but data from randomised controlled studies and ‘real-world’ data are sparse. The aim is to describe real-life data on outcomes and complications of our 12 years of clinical experience with Impella in patients with cardiogenic shock after acute myocardial infarction and to identify predictors of 6-month mortality. Methods: We describe a sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
53
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(66 citation statements)
references
References 36 publications
11
53
0
Order By: Relevance
“…However, as expected access-site complications occurred more frequently in the vaECMO group than in the Impella group. This finding is in line with previous investigations [14][15][16]. Recently, a large-scale propensity-matched, registry-based retrospective cohort study observational including 1768 patients with CS treated with Impella reported high rates of major bleeding of 31.3% [17], which was markedly higher compared to the bleeding rates in our Impella cohort.…”
Section: Discussionsupporting
confidence: 92%
“…However, as expected access-site complications occurred more frequently in the vaECMO group than in the Impella group. This finding is in line with previous investigations [14][15][16]. Recently, a large-scale propensity-matched, registry-based retrospective cohort study observational including 1768 patients with CS treated with Impella reported high rates of major bleeding of 31.3% [17], which was markedly higher compared to the bleeding rates in our Impella cohort.…”
Section: Discussionsupporting
confidence: 92%
“…The possibility of reducing the duration of ECLS has been reported by Scharge et al [50], however, in the experience of Pappalardo et al [48], the association of Impella and VA-ECMO prolonged the time of support but provided a successful recovery of patients who might not have survived under VA-ECMO treatment alone. The use of Impella has been associated with a significant risk of severe bleeding, vascular complications and cerebral stroke [53,54]. In patients receiving the dual treatment with VA-ECMO, a higher occurrence of hemolysis has been reported [48], however, no difference was generally found in terms of risk of major and minor bleeding, and cerebral stroke compared to VA-ECMO alone [47,49].…”
Section: Ecpellamentioning
confidence: 99%
“…On the other hand, real-world data are refractory. In the 12-year experience of the Amsterdam Medical Centre there was no significant improvement of survival when support was initiated before PCI [35].…”
Section: Discussionmentioning
confidence: 97%